Detection of edge component of threading dislocations in GaN by Raman spectroscopy. (22nd May 2018) - Kokubo, Nobuhiko; Tsunooka, Yosuke; Fujie, Fumihiro; Ohara, Junji; Hara, Kazukuni; Onda, Shoichi; Yamada, Hisashi; Shimizu, Mitsuaki; Harada, Shunta; Tagawa, Miho; Ujihara, Toru
Abstract: We succeeded in measuring the density and direction of the edge component of threading dislocations (TDs) in c -plane (0001) GaN by micro-Raman spectroscopy mapping. In the micro-Raman spectroscopy mapping of the E2 H peak shift between 567.85 and 567.75 cm −1, six different contrast images are observed toward directions of . By comparing X-ray topography and etch pit images, the E2 H peak shift is observed where the edge component of TDs exists. In contrast, the E2 H peak is not observed where the screw component of TDs exists.